Incidence of Postoperative Hypocalcemia following Total Thyroidectomy versus Completion Thyroidectomy. (2nd September 2014) - Merchavy, Shlomo; Forest, Veronique‐Isabelle; Marom, Tal; Hier, Michael P.; Mlynarek, Alex M.; McHugh, Tobial; Payne, Richard J.
Abstract : Objectives: Study hypocalcemia incidence and trends over time following completion thyroidectomy (CT) versus total thyroidectomy (TT). Methods: A retrospective study comparing hypocalcemia and hypoparathyroidism incidence rates in all patients who underwent CT and in a random control group of TT at the McGill University Thyroid Cancer Centre, during the period of 2007 through 2012. Data were collected for demographic, clinical, and pathological characteristics. Results: There were 68 CT patients and 146 TT patients. Transient hypocalcemia occurred in 1 out of 68 (2%) and 18 out of 146 (12%) inpatients in the CT and TT groups, respectively. The rate of hypocalcemia was significantly lower in the CT group when compared with the TT group ( P =. 02). In both groups, there were no cases of permanent hypocalcemia. In the CT group there were 12 (18%) patients with parathyroid gland or parathyroid tissue found in the surgical specimen, compared with 47 (32%) of patients in the TT group. There were no correlations between the postoperative hypocalcemia rates and the type of the thyroid disease or the numbers of parathyroid glands removed and found within the surgical specimen ( P >. 05). Conclusions: In this study, the risk of transient hypocalcemia in patients undergoing CT was significantly lower than the rate of hypocalcemia in patients undergoing TT.